An inter-laboratory comparison study on transfer, persistence and recovery of DNA from cable ties. (November 2017) - Steensma, Kristy; Ansell, Ricky; Clarisse, Lindy; Connolly, Edward; Kloosterman, Ate D.; McKenna, Louise G.; van Oorschot, Roland A.H.; Szkuta, Bianca; Kokshoorn, Bas
Highlights: DNA transfer and recovery from cable ties was studied by four laboratories. Impact of laboratory analysis and interpretation methods on results was examined. Amount of DNA recovered and DNA profile composition differed between laboratories. Inter laboratory differences may impact on weight of evidence at activity level. Abstract: To address questions on the activity that led to the deposition of biological traces in a particular case, general information on the probabilities of transfer, persistence and recovery of cellular material in relevant scenarios is necessary. These figures may be derived from experimental data described in forensic literature when conditions relevant to the case were included. The experimental methodology regarding sampling, DNA extraction, DNA typing and profile interpretation that were used to generate these published data may differ from those applied in the case and thus the applicability of the literature data may be questioned. To assess the level of variability that different laboratories obtain when similar exhibits are analysed, we performed an inter-laboratory study between four partner laboratories. Five sets of 20 cable ties bound by different volunteers were distributed to the participating laboratories and sampled and processed according to the in-house protocols. Differences were found for the amount of retrieved DNA, as well as for the reportability and composition of the DNA profiles. These differences also resulted in different probabilities of transfer, persistence and recovery for each laboratory. Nevertheless, when applied to a case example, these differences resulted in similar assignments of weight of evidence given activity-level propositions.